Jenseits der Epigonalität Selbst- und Fremdbewertungen im Artusroman und in der Artusforschung - Dietl, Cora 1967-; Schanze, Christoph 1982-; Wolfzettel, Friedrich 1941- (Schriften der Internationalen Artusgesellschaft, 2020)
Where does one draw the line between réécriture and epigonality? How do authors of Arthurian romance situate their own work between tradition and innovation? What criteria does literary scholarship later apply to classify an Arthurian romance as "masterful" or "epigonal"? The volume explores key instances of the shifting evaluation of Arthurian texts and the fundamental valency of literary judgment